Impaired Pre‐Motor Circuit Activity and Movement in a Drosophila Model of KCNMA1‐Linked Dyskinesia. Issue 5 (15th January 2021) - Kratschmer, Patrick; Lowe, Simon A.; Buhl, Edgar; Chen, Ko‐Fan; Kullmann, Dimitri M.; Pittman, Alan; Hodge, James J.L.; Jepson, James E.C.
Abstract: Background: Paroxysmal dyskinesias (PxDs) are characterized by involuntary movements and altered pre‐motor circuit activity. Causative mutations provide a means to understand the molecular basis of PxDs. Yet in many cases, animal models harboring corresponding mutations are lacking. Here we utilize the fruit fly, Drosophila, to study a PxD linked to a gain‐of‐function (GOF) mutation in the KCNMA1 /hSlo1 BK potassium channel. Objectives: We aimed to recreate the equivalent BK (big potassium) channel mutation in Drosophila . We sought to determine how this mutation altered action potentials (APs) and synaptic release in vivo; to test whether this mutation disrupted pre‐motor circuit function and locomotion; and to define neural circuits involved in locomotor disruption. Methods: We generated a knock‐in Drosophila model using homologous recombination. We used electrophysiological recordings and calcium‐imaging to assess AP shape, neurotransmission, and the activity of the larval pre‐motor central pattern generator (CPG). We used video‐tracking and automated systems to measure movement, and developed a genetic method to limit BK channel expression to defined circuits. Results: Neuronal APs exhibited reduced width and an enhanced afterhyperpolarization in the PxD model. We identified calcium‐dependent reductions in neurotransmitter release, dysfunction of the CPG, and corresponding alterations in movement, in model larvae. Finally, we observed aberrant locomotion and dyskinesia‐like movements in adult model flies, and partially mapped the impact of GOF BK channels on movement to cholinergic neurons. Conclusion: Our model supports a link between BK channel GOF and hyperkinetic movements, and provides a platform to dissect the mechanistic basis of PxDs. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society